Vitamin C Supplementation Improves Pulmonary Tuberculosis Patients' Sputum Conversion During Intensive Phase Category I Treatment in Medan - Elok Ariyani Safitri; Parluhutan Siagian; Bintang Yinke Magdalena Sinaga; Putri Chairani Eyanoer (Respiratory Science, 2022)
Background: Many factors influence the success of the acceleration of Acid-Fast Bacilli (AFB) sputum conversion in the treatment of the intensive phase of pulmonary tuberculosis (TB). One of these factors is the nutritional status or nutrition of pulmonary TB patients. Through a fenton reaction, Vitamin C is known to be able to sterilize Mycobacterium tuberculosis. This study aims to determine the effect of giving vitamin C on the conversion of AFB sputum in the intensive phase of pulmonary TB treatment. Method: This study was an inferential, quasi-experimental evaluation of the acceleration of AFB sputum conversion following vitamin C supplementation in patients with category I pulmonary TB. The study group was separated into two groups: 40 TB patients getting Anti Tuberculosis Treatment (ATT) with vitamin C, and 40 TB patients receiving ATT with placebo. Every two weeks, AFB sputum was examined, and vitamin C levels were measured before and after two months of therapy. Results: Conversion of AFB occurred sooner in the vitamin C group of pulmonary TB patients, with as many as 29 patients (72.5%) experiencing conversion of AFB sputum at the end of the second week of therapy, whereas there was no conversion in the placebo group. At the end of the fourth week, all patients (100%) given vitamin C showed AFB sputum conversion, whereas only eight patients (20%) in the placebo group had conversion at the end of the fourth week of treatment. Vitamin C levels increased significantly in the group of pulmonary tuberculosis patients who received vitamin C supplementation. Conclusion: Vitamin C supplementation in the treatment of pulmonary TB can accelerate the conversion of AFB sputum, which is statistically significant.